2018
DOI: 10.1021/acs.jafc.8b03468
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Liquid Chromatography–High-Resolution Mass Spectrometry for Pesticide Screening in Foods

Abstract: This perspective discusses the use of liquid chromatography coupled with high-resolution mass spectrometry (LC-HRMS) for multiresidue analysis of pesticides in foods and agricultural commodities. HRMS has the important distinction and advantage of mass-resolving power and, therefore, requires different concepts, experiments, and guidance for screening, identification, and quantitation of pesticides in complex food matrices over triple quadrupole mass spectrometry. HRMS approaches for pesticide screening, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 41 publications
1
55
0
3
Order By: Relevance
“…Wang et al demonstrated the extensive use of a full‐scan MS1 followed by mDIA in the effective and sensitive detection of pesticides or veterinary drugs in various food matrices. The equivalence of mDIA and vDIA experiments for pesticide screening has been evaluated . Although non‐targeted approaches using DIAs are effective and promising in multiresidue screening, there are still disadvantages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al demonstrated the extensive use of a full‐scan MS1 followed by mDIA in the effective and sensitive detection of pesticides or veterinary drugs in various food matrices. The equivalence of mDIA and vDIA experiments for pesticide screening has been evaluated . Although non‐targeted approaches using DIAs are effective and promising in multiresidue screening, there are still disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…An intermediate strategy between AIF and "Top N" DDMS2 for non-targeted data acquisition termed "data-independent acquisition" (DIA) has been developed with hybrid HRMS instruments for the analysis of food contaminants. [19][20][21][22][23][24][25][26][27][28][29][30] In general, with DIA data collection, a limited group of precursor (MS1) ions are sequentially filtered through a quadrupole (with a wide isolation window) and then introduced into the collision cell to produce product (MS2) ions. DIA can also be performed with TOF instruments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La necesidad de contar con esta información previa para incluir a los compuestos de interés en listas de búsqueda para su detección y análisis target impide el uso de estos sistemas para la búsqueda de otros compuestos que puedan estar igualmente presentes en la muestra a analizar, como metabolitos de plaguicidas, micotoxinas conjugadas, o compuestos de cuya presencia se tiene certeza pero que simplemente no se dispone de los estándares de calibración respectivos. Otros aspectos negativos de este tipo de analizadores son que por tener una resolución de masa unitaria a veces se hace imposible la identificación inequívoca de analitos que presentan transiciones isobáricas [143], que la determinación de un gran número de compuestos es un proceso que insume mucho tiempo, y que el número de transiciones MRM que pueden ser analizadas en una misma corrida está limitado por el tiempo que lleva medir una transición (el dwell time), el ancho del pico cromatográfico, el número de puntos por pico necesarios y la cantidad de analitos que co-eluyen [65,144]. La necesidad de analizar exhaustivamente un número cada vez más grande de residuos y contaminantes ha llevado al desarrollo de espectrómetros de masa de alta resolución como los analizadores de tiempo de vuelo (ToF) y el de trampa iónica orbital (Orbitrap), que permiten hacer screening de compuestos mediante la adquisición de espectros full-scan (escaneo completo) de alta sensibilidad, combinado con una alta exactitud de masa (típicamente <5 ppm), rápida adquisición de datos, con la posibilidad de realizar análisis non-target (no específicos, de compuestos desconocidos) y análisis retrospectivo de compuestos que inicialmente no fueron considerados a partir de los espectros full-scan obtenidos, permitiendo de este modo la determinación, en base a su masa exacta, de casi cualquier compuesto ionizable presente en el extracto de muestra [65,145].…”
Section: Páginaunclassified
“…Adicionalmente, la implementación de sistemas HRMS híbridos como el cuadrupolo-tiempo de vuelo (Q-ToF) y el cuadrupolo-Orbitrap (Q-Orbitrap) amplían el alcance de los métodos ya que además de medir masa exacta con análisis full-scan de alta resolución, ofrecen la posibilidad de realizar análisis target (MS/MS) para confirmación [143]. Esto permite conformar verdaderas plataformas analíticas multi-residuo multi-clase para la medición a gran escala de plaguicidas, micotoxinas, y otros contaminantes en aplicaciones cuantitativas o de screening de compuestos.…”
Section: Páginaunclassified